Prediksi Persediaan Perlengkapan Hewan Peliharaan Pada Toko Poopy Cat Store Menggunakan Algoritma Apriori - Muliati Badaruddin; Santoso Santoso (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2021)
Pets such as tame animals of various types such as cats, dogs, rabbits and others are one of the pleasures for animal lovers in having a desire to meet the needs and protect the animal from everything, difficulty in predicting the tendency of the breed. the goods to be purchased by consumers make shop owners often run out of items that are needed by consumers, this is because buyers do not make transactions and can reduce profit income to the store so it is necessary to extract information on data on buying and selling data or transaction data, in the application of extracting information using data mining methods with the APRIORI algorithm approach which is able to assist in finding out items of pet equipment from the number of sales, the results obtained from using this algorithm show the combination of the most frequent purchases carried out simultaneously on the supply of pet equipment so that it shows items that need to be stocked up more, the results obtained meet the previously set support and confidence values of 25% and 50%, the results obtained by 3 items Bolt 10 gr, Cage, Bowl get the highest value of 65%